Nursing care manual for pre and post-operative cholecystectomy patients: elaboration and evaluation (Research, Society and Development, 2021)
Objective: to develop and evaluate a nursing care manual for patients in the pre- and postoperative period of cholecystectomy. Methodology: study based on a development project that followed eight methodological steps and the evaluation was carried out by 48 participants, including professors, nurses, students, patients and family members, at a federal university and a university hospital in southern Brazil. The analysis was through simple and absolute frequencies for closed answers and for open answers we used the Discursive Textual Analysis. Results: unanimously, the participants believe that the information contained in the manual is important, in addition to the fact that the way the information is arranged is adequate and the illustrations contribute to a better understanding of the text. Conclusion: the use of the manual is valid when it encourages health education; shows the care/procedures to be performed and provides well-being.